Dam Safety: Highlighted Issues and Reliable Assessment for the Sustainable Dam Infrastructure - Bashar N.A.M.; Zainol M.R.R.M.A.; Aziz M.S.A.; Mazlan A.Z.A.; Zawawi M.H. (Springer Science and Business Media Deutschland GmbH, 2024)
Future dam infrastructures, especially those of older design, are vulnerable to climatic instabilities, natural hazards, flood risks and other internal and external factors. The operated dam should be protected from these factors to ensure continuous water supply, flood control and stable renewable power generation. Efficient management, safe operation, special contingency plans, advanced monitoring tools and techniques, and rehabilitation measures (non-structural and structural) for dams are considered important to achieve the highest safety standards. This comprehensive review provides a broad overview of dam safety under climate change and the implications for dam behaviour, hydraulic flow characteristics and downstream mapping (flood discharge, erosion, sedimentation, environmental, social and economic impacts). Climate change can affect the structural integrity of dams over short and long-term periods. Furthermore, a better understanding of the cause-effect relationship is needed to predict future impacts. Furthermore, this may lead to safety control approaches such as risk assessment, specific monitoring approaches, development of predictive models, modification of the existing dam structure and construction of structural measures. Therefore, the sustainability of dams can be achieved through the holistic involvement of all stakeholders, effective disaster management, continuous monitoring of structures and a comprehensive emergency plan. In addition, special inspections, surveys and regular maintenance are required to minimise risks. Therefore, non-countable and countable measures are needed to advocate for dam sustainability and support the United Nations Sustainable Development Goals (SDGs). The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.